2009
DOI: 10.1002/glia.20843
|View full text |Cite
|
Sign up to set email alerts
|

Theiler's virus infection induces TLR3‐dependent upregulation of TLR2 critical for proinflammatory cytokine production

Abstract: Theiler's murine encephalomyelitis virus (TMEV) infection directly induces many proinflammatory genes, including type I interferon (IFN) and a variety of cytokine genes. These virus-induced cytokines are a critical factor in developing TMEV-induced demyelinating disease. We have previously reported that the major activation signal for the cytokine genes is mediated via TLR3. In this study, we describe that TLR2 is upregulated via TLR3 signal and cooperatively participates in the expression of IL-6, IL-1β, CCL2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
60
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 52 publications
(74 reference statements)
0
60
0
Order By: Relevance
“…Our present study (Fig. 7) showed that the Th17 polarization can be achieved equally well in APCs from susceptible and resistant mice with agonists of multiple TLR receptors (TLR2, -3, -4, and -7), which are either known or suspected to be associated with the innate immune responses following TMEV infection (18,26,(29)(30)(31). Therefore, the potential deficiency of the signal induction in any of these TLRs is unlikely to be associated with the differential Th17 polarization.…”
Section: Discussionmentioning
confidence: 54%
“…Our present study (Fig. 7) showed that the Th17 polarization can be achieved equally well in APCs from susceptible and resistant mice with agonists of multiple TLR receptors (TLR2, -3, -4, and -7), which are either known or suspected to be associated with the innate immune responses following TMEV infection (18,26,(29)(30)(31). Therefore, the potential deficiency of the signal induction in any of these TLRs is unlikely to be associated with the differential Th17 polarization.…”
Section: Discussionmentioning
confidence: 54%
“…The overexpression of TLR2 has been shown to increase the release of inflammatory mediators from Theiler's virus-infected astrocytes (71). In this model, TLR2 is required for astrocytes to respond to media from infected astrocytes that had been UV irradiated to kill infectious Theiler's virus, suggesting that TLR2 responds to danger signals released by apoptotic cells (71).…”
Section: Discussionmentioning
confidence: 90%
“…NF-B activation following viral infection requires TLR3 and TLR2 (42,43) and is partially dependent on PKR (3,35). However, the induction of type I IFNs and IRF3/IRF7 activation, critical for type I IFN production, are not fully dependent on the presence of TLRs (43). These data indicate that other PRRs are also involved, either cooperatively or independently, in mediating TMEV-induced innate cytokine responses, particularly the production of type I IFNs.…”
mentioning
confidence: 92%
“…TMEV-induced cytokine gene expression, as well as viral replication, is dependent on the NF-B pathway (19,25,35). NF-B activation following viral infection requires TLR3 and TLR2 (42,43) and is partially dependent on PKR (3,35). However, the induction of type I IFNs and IRF3/IRF7 activation, critical for type I IFN production, are not fully dependent on the presence of TLRs (43).…”
mentioning
confidence: 99%